Field Trial Evaluations of a Switched Directional/Omnidirectional In-the-Ear Hearing Instrument - Preves, David A.; Sammeth, Carol A.; Wynne, Michael K. (Journal of the American Academy of Audiology, 1999)
The use of directional microphones is one of the few methods available for hearing aids to increase the signal-to-noise ratio. The smaller microphones available with today's technology have increased the viability of their application for in-the-ear (ITE) hearing aids. This study evaluated an ITE hearing aid containing two nondirectional microphones that provides wearer-selectable omnidirectional/directional operating modes. Ten sensorineural hearing-impaired patients were fitted binaurally. During the first trial period, the low-frequency gain decrease produced by the directional mode was not compensated for. The frequency responses were matched during the second trial period. For both trial periods, Hearing in Noise Test results using two uncorrelated noise sources indicated significant speech recognition improvements for the directional mode relative to the omnidirectional mode. Responses on Abbreviated Profile of Hearing Aid Benefit questionnaires, paired-comparison judgments, and interview data revealed that most subjects preferred the directional mode in noisier environments, but many also preferred the omnidirectional mode in quiet listening.Abbreviations: AGC-O = automatic gain control with output compression, APHAB = Abbreviated Profile of Hearing Aid Benefit, BTE = behind-the-ear hearing aid, CD = compact disc, Dl = Directivity Index, HINT = Hearing in Noise Test, ITE = in-the-ear hearing aid, MCL = most comfortable listening level, NAL-R = National Acoustics Laboratories' revised prescriptive formula, SNR = signal-to-noise ratio, UCL = uncomfortable loudness level
Keywords: Amplification; directional microphones; hearing aids; speech recognition